CRISPR-Cas9-Based Toolkit for Clostridium botulinum Group II Spore and Sporulation Research - Mertaoja, Anna; Nowakowska, Maria B.; Mascher, Gerald; Heljanko, Viivi; Groothuis, Daphne; Minton, Nigel P.; Lindström, Miia (Frontiers in Microbiology, 2021)
The spores of Clostridium botulinum Group II strains pose a significant threat to the safety of modern packaged foods due to the risk of their survival in pasteurization and their ability to germinate into neurotoxigenic cultures at refrigeration temperatures. Moreover, spores are the infectious agents in wound botulism, infant botulism, and intestinal toxemia in adults. The identification of factors that contribute to spore formation is, therefore, essential to the development of strategies to control related health risks. Accordingly, development of a straightforward and versatile gene manipulation tool and an efficient sporulation-promoting medium is pivotal. Our strategy was to employ CRISPR-Cas9 and homology-directed repair (HDR) to replace targeted genes with mutant alleles incorporating a unique 24-nt ‘bookmark’ sequence that could act as a single guide RNA (sgRNA) target for Cas9. Following the generation of the sporulation mutant, the presence of the bookmark allowed rapid generation of a complemented strain, in which the mutant allele was replaced with a functional copy of the deleted gene using CRISPR-Cas9 and the requisite sgRNA. Then, we selected the most appropriate medium for sporulation studies in C. botulinum Group II strains by measuring the efficiency of spore formation in seven different media. The most effective medium was exploited to confirm the involvement of a candidate gene in the sporulation process. Using the devised sporulation medium, subsequent comparisons of the sporulation efficiency of the wildtype, mutant and ‘bookmark’-complemented strain allowed the assignment of any defective sporulation phenotype to the mutation made. As a strain generated by complementation with the wildtype gene in the original locus would be indistinguishable from the parental strain, the gene utilized in complementation studies was altered to contain a unique ‘watermark’ through the introduction of silent nucleotide changes. The mutagenesis system and sporulation medium devised provides a solid basis for gaining a deeper understanding of spore formation in C. botulinum, a prerequisite for the development of novel strategies for spore control and related food safety and public health risk management.